Sustainable strive: Holistic exploration of CSR through economic, environmental, and social lenses - Aditya, Aji Fras Aditya Fras; Leniwati, Driana; Prasetyo, Adi; Juanda, Ahmad; Afrizal, Faris; Jati, Ahmad Waluya (Kompartemen : Jurnal Ilmiah Akuntansi, 2024)
This research explores the implementation of Corporate Social Responsibility (CSR) at PT Unilever Indonesia using a qualitative case study approach. It employs a comprehensive methodology to examine the economic, environmental, and social aspects of CSR integration in this multinational company. The study reveals how PT Unilever Indonesia’s CSR commitments contribute to economic growth, environmental conservation, and social welfare in Indonesia, aligning with the principles of the Triple Bottom Line. It also highlights the company’s recognition through three prestigious awards and examines the dynamics between profit, people, and the planet. Addressing a gap in existing research, this study significantly contributes to the broader discourse on CSR implementation, particularly in the context of an FMCG company operating in a complex environment like Indonesia. It sheds light on the evolving role of corporations in promoting sustainable development.